Evaluasi Penggunaan Media Tabung Angka Untuk Menstimulasi Kemampuan Mengenal Angka Anak Kelompok B - Jaya, Allan Firman; Janatin, Siti Uslifatul; Satrianta, Hengki (Student Journal of Early Childhood Education, 2024)
This research aims to evaluate the use of media used by teachers to stimulate the ability to recognize numbers in children which has been carried out well and in accordance with its function. The focus of this research is the results of the evaluation of the use of number tube media to stimulate the ability to recognize numbers and whether there are obstacles in using number tube media to stimulate the ability to recognize numbers. This research uses a qualitative approach. Data collection techniques use interviews, observation and documentation, inductive data analysis techniques. The research results show three main criteria in evaluating learning media, namely: quality of content and objectives, instructional quality, technical quality. All of them showed good results. The obstacles are limited time and children who tend to scramble to use the media